Solo disponible en BuenasTareas
• Páginas : 3 (644 palabras )
• Descarga(s) : 0
• Publicado : 13 de febrero de 2011

Vista previa del texto

10 de febrero del 2011. 5:33 pm

1) y=1+1x -1=1x+1x
f(y)1=-11+1x2 1+1x -2=-[1+1x2 1x2+2+1x2]
f(y)1=1x2+2+1x2+1x4+2x2+1
2) fx=4x4-2 =x4-214f1x=14x4-2-344x3-0=4x344(x4-2)3 =x34(x4-2)3
3) fx=x2+5x-33=
f1x=3x2+5x-332x+5dx=6x+15x2+5x-33
4) fx=13x+23
f1x=313x+2213= 3313x+22=13x+22
5) y=4x2-12x9x+8
y1=4x2-12x9+9x+88x-12y1=36x2-9x2+72x2-9x2+64x-82
y1=108x2+55x-4
6) x33x+1
x33+3x+13x2
3x3+9x3+3x2=12x3+3x2
7) ft=1-2t1+2t
f1t=121-2t1+2t 1+2t-2-(1-2t(2)1+2t2
f1t=121-2t1+2t -2-4t-2+4t1+2t2=-421-2t1+2t 1+2t2-21+2t1-4t2
8) fw=w-3w+22
9) fx=4xb2a-bx
f1x=2a-bx4-4xb-b2a-bx2=8ab-24xb+24xb2a-bx2=
8ab(2a-bx)2
10) fx=x2-9x-3

f1x=2xx-3-x2-912x-3 x-32
f1x=x-32x-x2-92x-3 x-32
11)fx=aba2-t2
fx=ab12a2-t2 -2x=-2bx2aa2-t2

1) Y= Sen 8X

Y’= Sen 8X = Cos 8X (d 8X) = Cos 8X (8) = 8Cos 8X
dx

2) f(X) = Cos3X2

f(X)=Cos 3X2 = -Sen 3X2 (d3X2) = - Sen 3X26X = -6XSenX2
dx

3) f(X) =Tan X3

f(X) = TanX3=Sec2 Tan X2 d 3X2 = 3X2 Sec2 TanX3
dx

4) S(t) = Sec 6 t
S(t) = Sec 6t = Sec6t Tan6t (d 6t) = Sec6t Tan6t(6) = 6 Sec 6t Tan6t
dx

5) f(X) = Cot 4X3
f(x) =Cot4X3= -Csc2 4X3 (d 4X3) = -Csc2 4X3 (12X2) =-12X2 Csc2 4X3dx

6) f(X) = Csc 9X
f(X) =Csc 9X= -Csc9X Cot9X (d 9X) =-Csc9X Cot9X (9)= -9 Csc9X Cot9X
dx7) f(X) =Cos aX
f(X) =Cos aX = -Sen aX (d aX)= -Sen aX (1)= -1Sen aX
dx

8) S(t) Tan bt2
S(t) Tan bt2= Sec2bt2 (d bt2) =Sec2bt2 (2t) = 2t Sec2bt2...